Pemikiran Pierre Bourdieu dalam Memahami Realitas Sosial - Mega Mustikasari; Arlin Arlin; Syamsu A Kamaruddin (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study is to find out Bourdieu's thoughts, as an introduction to understanding social reality. This study introduces the basic ideas of Bourdieu's thinking in understanding how individuals relate to form "practices". How does this "practice" occur and what is "involved" in that "practice", and what are the relations of habitus, arena, capital, practice and power in Bourdieu's view. The results of this study show that Pierre Bourdieu is one of the leading theorists whose ideas are used in cultural studies. Bourdieu's thinking was heavily influenced by Aristotle, Thomas Aquinas, Hegel, Marx, Durkheim, Max Weber, Picasso, Franz Fanon, Jean Paul Sartre, Husserl, Ferdinand de Saussure, Levi Strauss, Wittgenstein, Martin Heidegger, Michel Foucault, etc. The conclusion of the research is that Bourdieu concocted the thoughts of several thinkers into a new form of thinking that emphasizes the role of actors or subjectivity, which is known as the structural-constructive method. Bourdieu is known for developing cultural sociology studies and reflective sociology or metasociology. Keywords: Thoughts of Pierre Bourdieu